PSYCOEDUCATION OF YOUNG MOTHER TO REDUCE ANXIETY OF HYPERTENSIVE ELDERLY IN PUTON VILLAGE WORKING AREA OF CUKIR HEALTH CENTER: PSIKOEDUKASI IBU MUDA UNTUK MENURUNKAN KECEMASAN LANSIA HIPERTENSI DI DESA PUTON WILYAH KERJA PUSKESMAS CUKIR - Fitri Firranda Nurmalisyah; Siswati; Desy Siswi Anjar Sari; Heni Maryati; Mumpuni Dwiningtyas (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
The elderly are a vulnerable age group, where in this phase a person tends to experience a decline in both physical and mental function and thus requires assistance to fulfill daily life activities. Health problems such as high blood pressure (hypertension), diabetes (diabetes mellitus/DM), heart disease, etc. can cause the elderly to be unable to carry out activities and fulfill their daily needs, thus requiring long-term care (PJP). A systematic program is needed to care for the elderly so that their needs can be met, prevent complications, and maintain optimal quality of life for the elderly. At the stage of development of the elderly, individuals experience setbacks both physically, psychologically and socially. Dependence on other people, especially family, becomes very high. Therefore, specific and appropriate assistance is needed to help the elderly carry out their activities optimally and not cause worse conditions or complications. Efforts that have been made to prevent and control hypertension in the elderly include providing psychoeducation to young mothers accompanying the elderly. Bearing in mind that in Puton Village the incidence of hypertension is still high and many people complain of experiencing anxiety due to hypertension. This community service activity was carried out for 1 week starting from the coordination stage to the evaluation. Based on the results of community service, participants understand more about anxiety in elderly people with hypertension so that they can reduce anxiety in elderly people with hypertension and increase the knowledge and ability of young mothers in caring for the elderly at home